"Value creation" by allocation of resources in SMEs under different conditions of economic development. (25th May 2005) - Schmidt, Karl-Heinz
The long term development of economic activities and economic thought demonstrates that the earlier research on "values" and "value creation" brought about different, even antagonistic theoretical approaches. Three main versions of "economic value" were identified: exchange value, user value and returns value (Hubig/Muller, 1989). Taking into account also the dimensions of value – objective and subjective value – (Stavenhagen, 1969, p.53 f, 227 ff), the impact of economic resources on the creation of value turns out to be a severe problem in economic reasoning especially if entrepreneurship and SMEs are considered (Dobb, 1977, esp. p.185 ff). The following contribution is restricted to two specific aspects of the relations between allocation of resources and value creation: the changes of theoretical hypotheses of value creation and empirical findings on value creation by allocation of resources in SMEs of Germany, Japan and South Africa.